The bone clocks : a novel - Mitchell, David (David Stephen) (New York : Random House, 2014)
Following a scalding row with her mother, fifteen-year-old Holly Sykes slams the door on her old life. But Holly is no typical teenage runaway: a sensitive child once contacted by voices she knew only as "the radio people," Holly is a lightning rod for psychic phenomena. Now, as she wanders deeper into the English countryside, visions and coincidences reorder her reality until they assume the aura of a nightmare brought to life. For Holly has caught the attention of a cabal of dangerous mystics -- and their enemies. But her lost weekend is merely the prelude to a shocking disappearance that leaves her family irrevocably scarred. This unsolved mystery will echo through every decade of Holly's life, affecting all the people Holly loves -- even the ones who are not yet born. A Cambridge scholarship boy grooming himself for wealth and influence, a conflicted father who feels alive only while reporting from occupied Iraq, a middle-aged writer mourning his exile from the bestseller list -- all have a part to play in this surreal, invisible war on the margins of our world. From the medieval Swiss Alps to the nineteenth-century Australian bush, from a hotel in Shanghai to a Manhattan townhouse in the near future, their stories come together in moments of everyday grace and extraordinary wonder.
2015 World Fantasy Award.
Keywords: Mystics -- Fiction; Imaginary wars and battles -- Fiction; Science fiction; Skyes, Holly (Fictitious character); FICTION -- Literary; FICTION -- Science Fiction -- General; FICTION -- Fantasy -- General; Imaginary wars and battles; Mystics; Andrae, A; Englisch, ...; Imaginary wars and battles -- Fiction; Runaways -- Fiction; Science fiction; Science fiction; Fiction; Science fiction; Science fiction